Energy characterization of 100m maximal front crawl - Ribeiro, J.; Sousa, A.; Figueiredo, P.; Clemente, V.; Pelarigo, J.; Monteiro, J.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Sports Science & Medicine, 2012)
The majority of studies that assess the oxygen consumption (VO2) kinetics in swimming are conducted at the moderate and heavy intensity domains; at faster paces, VO2 dynamics assessment is still scarce and a challenging task. Despite it has been suggested that aerobic energy contribution is greater than 50% even at short duration efforts, little is known about the relative contribution of the different energy systems at short swimming distances. In addition, the contribution of the legs action on swimming propulsion is often depreciated due to the additional energy expenditure, without evident benef ts for propulsion; however, over short duration swimming, exercise economy is usually assumed to be of secondary importance. The purpose of the present study was to characterize the VO2 kinetics, determine the relative contribution of the three energy sources, and to analyse the effect of legs action on energy cost (C) and performance, on 100m maximal front crawl. Methods: Ten trained swimmers (19 ± 1.38yrs, 181.42 ± 3.45cm, 72 ± 2.56kg) performed 2x100m front crawl allout with 24h in-between, the 1st swimming freely and then performing with "arms only" (legs supported by a pull-buoy). VO2 was measured by a K4b2 portable gas analyser connected to the new AquaTrainer respiratory snorkel (Cosmed, Italy), and capillary blood lactate was taken at rest and during the recovery period (Lactate Pro, Arkay Inc., Japan). C was calculated as the ratio between energy expenditure (aerobic + anaerobic lactic + anaerobic alactic pathways) and corresponding velocity. VO2 data was fitted using the following mono-exponential model: VO2 = VO2Basal + VO2Amplitude*(1-e(- time/time constant)). Results: An instantaneous and sudden increase in the VO2 occurred from the beginning of the effort, with mean±SD for VO2peak, VO2Amplitude, and time constant being 54.27 ± 3.80 and 41.14 ± 5.59 ml/min·kg, and 11.32 ± 3.02s, respectively. The relative energy sources contributions were 41.61, 34.78 and 23.61% for the aerobic, anaerobic lactic and anaerobic alactic pathways. Task complexity constraints and lower maximal velocity may account for some hypothetical overestimation of the aerobic contribution in a 100m competitive event. C for whole body swimming was higher than swimming with arms only (0.85 vs 0.65kJ/m), and the magnitude of the legs contribution for performance was 14.1%. Conclusions: Despite the short duration of the 100m front crawl event, swimmers were able to attain high values of VO2peak and VO2Amplitude, and the aerobic energy system was found to be predominant. Notwithstanding the higher C, legs action revealed to have an important propulsive contribution.